2015
DOI: 10.1007/s11295-015-0884-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimating heritability of disease resistance and factors that contribute to long-term survival in butternut (Juglans cinerea L.)

Abstract: For most wild species affected by exotic pests or pathogens, the relative importance of heritable genetic differences in determining apparent variation in disease resistance is unknown. This is true in particular for butternut, a North American hardwood affected by butternut canker disease and undergoing demographic contraction. Little is known about site effects on butternut decline, in part because long-term monitoring data are lacking. We collected detailed disease phenotypes and multilocus microsatellite g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
0
13
1
Order By: Relevance
“…Although there may be some variation in the heritability of resistance, there are no studies demonstrating heritable resistance to butternut canker disease. One study demonstrated little genetic basis for observed differences in mortality (LaBonte, Ostry, Ross‐Davis, & Woeste, ). Instead, LaBonte et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there may be some variation in the heritability of resistance, there are no studies demonstrating heritable resistance to butternut canker disease. One study demonstrated little genetic basis for observed differences in mortality (LaBonte, Ostry, Ross‐Davis, & Woeste, ). Instead, LaBonte et al.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, LaBonte et al. () concluded that localized site conditions were more useful predictors of butternut mortality with greater survival in drier, upland sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study, in contrast, included seeds propagated from long-term surviving selections collected from across a wide geographic range and inter-pollinated together in a grafted orchard, expanding the genetic diversity of our test families. Additionally, our study did not include environmental and site factors as in Labonte et al (2015), so a comparison with the current study's results on heritability of BCD tolerance in hybrids is not entirely possible.…”
Section: Tolerance Of Juglans Cinerea and Its Hybridsmentioning
confidence: 94%
“…With differing levels of aggressiveness, the specific isolates present within a certain location may contribute, in part, to help explain why some areas experience more severe and sudden BCD outbreaks than others (Broders et al, 2015;Morin et al, 2017). However, it is likely that habitat and environment also play a strong role in determining occurrence of infection in these situations as well (Boraks and Broders, 2014;Labonte et al, 2015;Morin et al, 2017).…”
Section: Effect Of Fungal Isolatementioning
confidence: 99%